Comparative and Translatorly - Anna Rosen Guercio ([sic])
World literature’s natural home is comparative literature, a discipline born from and shaped by, as Vilashini Cooppan elegantly puts it, “scholarly engagements with the categories of migration, exile, diaspora, and globalization” (15). However, world literature has frequently been framed as a problem for the discipline, in large part because of its dependence on the ever-vexing and still mistrusted specter of translation. In light of the long-standing anxiety toward both world literature and translation, I propose here that comparatists do ourselves a terrible disservice if we do not urgently take up the questions raised by this disciplinary tension. Translation – in all of its attendant struggles with ethics, aesthetics, appropriation, authority – is not the problem, but, rather, should be understood as a key critical lens for comparative and world literature.In order to establish academia’s frustration with this subject, one need look no further than the “Three Reports to the America Comparative Literature Association on ‘Professional Standards’” (dating from 1965, 1975, and 1993), which return repeatedly to the problem of reading translated literature, circling around it with intense ambivalence. The moral of their story seems to be that translated texts are integral to comparative literature at the same time that they threaten its existence by undermining disciplinary exclusivity in foreign language expertise and by shining a sort of spotlight on all that literature which comparative literature may sometimes “condone” (as one of the reports puts it) but to which it does not often actively attend. Even Goethe had Western European languages and literatures firmly in mind when he coined the term, “Weltliteratur.” Translations can’t help but point up the limits of the “four [likely European] languages” proposed as minimal standards for graduate students by the Green and Bernheimer reports, and on the strength of which a comparative literature department would presumably distinguish itself from departments of English, media studies, and so on. The discipline, one comes to understand, must hold translation at arm’s length, or, preferably, secreted behind its back, embarrassed that it can’t just give the mess up.